Caring for calves: Canadian public perspectives of calf handling methods during spring processing - Goldhawk, Christy; Adams, Cindy; Pajor, Ed (Frontiers in Animal Science, 2024)
In North American beef production, handling and restraint of young calves is integral to animal welfare and management practices. This study used a mixed-method approach to gather public perceptions of three handling and restraint methods common in western Canada during spring processing (TT—tilt table, RW—roping and wrestling, and NF—roping and NordFork). Canadians (n = 551) participated in an online survey that included videos of each handling method to ascertain preferences and acceptability. Participants were given industry information about handling and restraint or generic information regarding hay as a control information statement within the topic of agriculture. The survey also collected information about knowledge of the beef industry, animal welfare, and empathy toward animals. The reasons for preferences for specific handling methods were described as the presence of a perceived positive attribute and the absence of a perceived negative for most preferred methods, and inversely when explaining the least preferred method. The main themes focused on the calf’s experience, perception of handler actions, and pragmatic balancing of needs for a good life for the calf. All methods were rated as more acceptable for participants that ate meat consistently, knew more about the beef industry, and, to a lesser extent, if the individual had a lower animal empathy score. Acceptability was not affected by providing information about the practices; however, information did elicit more pragmatic reasoning. Most participants preferred TT over NF and RW (p < 0.001) and found TT more acceptable as well (p < 0.001). The TT was the most preferred method due to calf experience and human handling—notably the absence of dragging a calf, which was predominant in why participants selected NF or RW as their least preferred method. Consistency of themes highlights that regardless of method or acceptability, the fundamental expectation of the public focuses on the perception of the calf’s quality of life, humane handling, and pragmatism, which are values aligned with beef sustainability initiatives.